Canon Onaindia's evidence (press cutting) - Onaindia, Alberto de
013-0005-001 Catholic Herald 4 Dec. '42 CANON ONAINDIA'S EVIDENCE Sir, — With reference to the letter from Lt.-Col. P.W. O'Gorman, which appeared in The Catholic Herald of November 27, under the heading of "The Guernica Calumny," I should like to make the following observations. I am a Basque Catholic priest, and at the request of Mgr. Mujica, then Basque Bishop of Vitoria (exiled by the Franco authorities) I as a witness, sent a sworn statement regarding the bombing of Guernica to Cardinal Pacelli, then Secretary of State of the Vatican, the present Pope. In answer to Lt-Col O'Gorman's statements, I swear before God : 1. That I personally was in Guernica on April 26, 1937, during the bombing by planes from the Franco zone, from 4.15 p.m. to 7.30 p.m. 2. That I was a witness of the attack, which took place on market day when the town was full of people. The first bombs fell in the streets adjoining the station, then a single plane flew over several times machine-gunning the people in the streets and in the fields outside the town. This was followed by waves of heavy bombers at approximately eight-minute intervals, dropping explosive and incendiary bombs. They were flying so low that with my own eyes I could see the bombs as they left the planes. Having sworn to the above, perhaps I may be allowed to make some comments upon Lt.-Col O'Gorman's letter. Firstly, all the eye-witnesses, who have made statements and who were in Guernica on that day, even the supporters of Franco, have all affirmed that it was destroyed by aerial bombardment. All those who assert that it was burnt by the Basques were not there on April 26, but visited the town some time later. Secondly, in the " scorched-earth" policy, as carried out by the Russians, and by the British forces in Malaya, it has never been the practice to burn their own people, the wives, children and parents of the retreating forces. In the bombardment of Guernica there were more than 500 casualties, nearly all women and children and old people, relatives of the two Basque battalions stationed there. Is it likely that the Basques would have killed their own families? Thirdly, there were, it is true, two temporary barracks and small war factories. These, the only military objectives, were not, however, in the town itself, but on the outskirts, and were untouched by the bombardment. Lt.-Col. O'Gorman mentions Sir Page Croft's statement that the Town Hall with archives and the famous tree was unscathed. I must, however, point out that the tree is some distance from the Town Hall, beside the old Parliament House, with which Sir Page Croft no doubt confused it. The Town Hall with all its archives was completely destroyed. It received three direct hits, and many people sheltering there were killed. The writer of the letter ignores the later German admission that their planes bombed Guernica. In this connection I should like to mention a conversation I had with Count Ciano, in the course of which he said : " You are Canon Onaindia, I have read that you were in Guernica during the bombardment. The Italians did not destroy Guernica." I replied : " The Germans did," and he answered : " Let it be known, not the Italians." I also have a personal letter from Cardinal Goma, the late Primate of Spain and a supporter of Franco, answering my protest against the attack on Guernica, in which he asked me to negotiate the surrender of Bilbao, adding that otherwise " Guernica was a terrible warning of what would happen to the great city (Bilbao)." A. de Onaindia. Canon, D.D., Ph.D. 14, Kendall Avenue South. Sanderstead, Surrey. 292/946/13/5(i)